(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Among other applications, austenitic stainless steel is frequently used in heat exchangers, furnace and in aircraft engine parts. It has chromium and nickel in it. Austenitic stability over a wide temperature range and strong corrosion resistance are both facilitated by nickel and chromium respectively. It is typically applied to process streams that contain chloride or halide. The impact of parameters on the weld joint for 316 austenitic stainless steel welding with tungsten inert gas was investigated in this work. Welding settings influence the weld’s mechanical qualities. Determining the ideal welding circumstances for obtaining the highest tensile strength was the aim of optimization.